Bio-Floc Technology: Prospects & Challenges in Fish Farming of Nepal - Neupane, Prajina; Adhikari, Madhusudhan; Thapa, Manita Kumari; Pandeya, Astha Kiran (International Journal of Applied Sciences and Biotechnology, 2020)
Bio-floc technology is the blue revolution in aquaculture & new technique of enhancing water quality & utilizing feed wastes in the aquaculture system. It follows the concept of conversion of ammonium in addition to organic nitrogenous wastes into bacterial biomass in where heterotrophic bacterial growth is stimulated & nitrogen uptake through the production of microbial proteins is promoted by the addition of carbohydrates to the pond. Nitrogen generated by uneaten feed and excreta of cultured organisms is converted into proteinaceous feed available for those same organisms. This technique recycles nutrients & nitrogenous wastes by maintaining a high carbon: nitrogen ratio and provides essential & higher quality nutrition to the shrimps & fishes in achieving fast growth, lesser FCR & possibility to prevent diseases. Water requirement in BFT is extremely less & it is advantageous than the conventional system where there is continuous water & nutrient recycling, lower FCR. On the other hand, many challenges are existing in practicing bio-floc in Nepal as it requires frequent pond monitoring by the technical manpower. The choice of carbon source should be made wisely and correctly as the performance of fish and water quality in the bio-floc ponds depend highly upon carbon source. Further, vitamins required for fish may not be produced by microbes thus needed to identify them and supply through the feed. However, the practice of bio-floc technology will be proven worth for farmers in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 140-145